2015
DOI: 10.5897/ajmr2015.7388
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical, microbiological and heavy metal studies on water samples and bacteria obtained from Dandaru River in Ibadan, South-western Nigeri

Abstract: The physicochemical, microbiological and heavy metal studies of water samples and bacteria obtained from the Dandaru River were investigated. Water samples were collected from six different sampling points along the course of the river and analysed using standard procedures. The physicochemical parameters showed that the water samples at point 5 had the highest value for all the parameters except Total Dissolved Solids. The heavy metal analysis revealed that the mean concentration of zinc, lead, chromium and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 5 publications
2
6
1
Order By: Relevance
“…However, the value of the heterotrophic count in this study (0.9 × 10 7 ) is higher than the 1.2 × 10 6 as it was reported by Ogbonna [32]. However, a lower total bacterial count (3.6 -6.4 × 10 1 ) compared to the one observed in this study was reported by Adekanmbi and Falodun [28], in a study carried out on water samples collected from a river that is close to a tertiary hospital with human activities such as car washing, laundry, bathing, swimming and fishing influencing its quality, but the present study was carried out on abattoir wastewater, however, similar activities were observed in both instances.…”
Section: Antibioticscontrasting
confidence: 56%
“…However, the value of the heterotrophic count in this study (0.9 × 10 7 ) is higher than the 1.2 × 10 6 as it was reported by Ogbonna [32]. However, a lower total bacterial count (3.6 -6.4 × 10 1 ) compared to the one observed in this study was reported by Adekanmbi and Falodun [28], in a study carried out on water samples collected from a river that is close to a tertiary hospital with human activities such as car washing, laundry, bathing, swimming and fishing influencing its quality, but the present study was carried out on abattoir wastewater, however, similar activities were observed in both instances.…”
Section: Antibioticscontrasting
confidence: 56%
“…Except at sampling point 1 with 0.38mg/l, the lead content of the river is within the SON and WHO permissible limits of 0.1mg/l. this is in agreement with the report of other researchers during similar studies [10] [24] [25] reported a higher level of 3.59mg/l.…”
Section: Discussionsupporting
confidence: 94%
“…The results of the physicochemical analysis of the water samples as presented in Table 1 showed that the pH values recorded are within the World Health Organization, WHO permissible limit of 6.5 -8.5 and Federal Environmental Protection Agency (FEPA) permissible limit of 6.0 -9.0. This observation is also similar to the pH value range of 7.8-8.2 reported in Turkey [9] and Ibadan, Nigeria [10] but lower compared to the range of 7.4 -10.0 reported from another study in Turkey [11]. The pH of water is very important in that changes in pH values may affect the toxicity of microbial poisons in the water [12].…”
Section: Discussionsupporting
confidence: 85%
“…Various genera of metal-resistant bacteria have been isolated from different sources notably wastewater. Several authors have reported the isolation of metalresistant bacteria from various sources [7,[16][17][18]. Bacteria adapt to metal stress in their environment and respond to it by developing several resistances or coping mechanisms to its toxicity [19].…”
Section: Discussionmentioning
confidence: 99%